The Greening of Anthocyanins: Eco-Friendly Techniques for Their Recovery from Agri-Food By-Products - Mariacaterina Lianza; Lorenzo Marincich; Fabiana Antognoni (MDPI AG, 2022)
In recent years, several steps forward have been made toward a more sustainable approach for the extraction of bioactive compounds from plant materials based on the application of green extraction principles. It is currently recognized that waste and by-products deriving from agriculture and food industries still contain a wide array of high value-added substances, which can be re-used to obtain new products with various applications in the food, supplement, pharmaceutical, and cosmetic industries. Anthocyanins are a class of these valuable metabolites; they confer the red, violet, and blue color to fruits and vegetables, and scientific evidence has accumulated over the last few decades to support their beneficial effects on human health, in great part deriving from their powerful antioxidant capacity. This review provides a general overview of the most recent green procedures that have been applied for the recovery of anthocyanins from plant-derived wastes and by-products. The most widely used green solvents and the main sustainable techniques utilized for recovering this class of flavonoids from various matrices are discussed, together with the variables that mainly impact the extraction yield.